Biological Treatment of Organic Waste in Wastewater-towards a Circular and Bio-Based Economy - Garfí, Marianna (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue focused on innovative solutions for the biological treatment of organic waste from wastewater. In particular, research articles included in this SI are related to: Process mechanisms and operation, optimization, monitoring, modeling, and applications; Removal of pathogens and emerging pollutants; Reuse and circular economy; Resource recovery (e.g., nutrients recovery, high-value compounds) and energy valorization (e.g., biogas); Life cycle assessment and carbon footprint; Technoeconomic assessment and social perception of waste-to-resource processes; Low-cost technologies; Policy. Overall, this SI provides new ways to valorize organic waste from wastewater and describe novel processes as well as the environmental and social benefits in the frame of the Sustainable Development Goals.